TikTok social media marketing and beauty influencers' impact on skintific purchase decisions through brand awareness - Alika, Florensia; Listiana, Erna; Afifah, Nur; Juniwati, Juniwati; Mayasari, Endah (Institute of Computer Science (IOCS), 2024)
The beauty industry is currently growing very rapidly, with many new products competing for consumer attention. The objective of this study was to ascertain and examine the impact of TikTok social media marketing, beauty influencers, and brand awareness as mediating variables on the form of Skintific product purchasing decisions. The research method used is quantitative research with explanatory research design. The population of this study consists of all consumers of Skintific brand products. This research uses purposive sampling. Data for this study will be collected through a questionnaire distributed through various social media platforms to people over 17 years old and Skintific products are used and purchased by TikTok social media users in Indonesia. To examine the correlation between factors, this study uses Structural Equation Modeling (SEM) with AMOS 24. The findings of this study indicate that social media marketing and beauty influencers significantly and positively impact purchasing decisions. Brand awareness positively and significantly affects purchasing decisions through social media marketing and beauty influencers.